2018
DOI: 10.1097/mog.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Myths and realities about alcohol and smoking in chronic pancreatitis

Abstract: Obtaining accurate history, appropriate evaluation and management can help to achieve meaningful improvement in symptoms in patients with chronic pancreatitis. Abstinence from alcohol and smoking cessation, when applicable, should be recommended in all patients to prevent disease recurrences and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 52 publications
0
20
0
4
Order By: Relevance
“…99 What is sobering is that approximately 20%-40% of children with ARP will quickly progress, within 2-5 years of the start of AP, to a diagnosis of CP. 13,100 Although there are currently few data on the role of smoking or alcohol on pediatric pancreatitis progression, based on the alarming rates reported with these toxins in adults with pancreatitis, 101 we generally proscribe their use in children with ARP. Longitudinal studies are necessary in patients diagnosed with pancreatitis during childhood to ascertain the natural history of progression from ARP to CP, then EPI and diabetes, and potentially pancreatic cancer and, importantly, to identify the determinants that accelerate and, conversely, retard progression.…”
Section: Prognosis and Natural Historymentioning
confidence: 99%
“…99 What is sobering is that approximately 20%-40% of children with ARP will quickly progress, within 2-5 years of the start of AP, to a diagnosis of CP. 13,100 Although there are currently few data on the role of smoking or alcohol on pediatric pancreatitis progression, based on the alarming rates reported with these toxins in adults with pancreatitis, 101 we generally proscribe their use in children with ARP. Longitudinal studies are necessary in patients diagnosed with pancreatitis during childhood to ascertain the natural history of progression from ARP to CP, then EPI and diabetes, and potentially pancreatic cancer and, importantly, to identify the determinants that accelerate and, conversely, retard progression.…”
Section: Prognosis and Natural Historymentioning
confidence: 99%
“…Although excessive alcohol consumption has long been known to be the primary cause of chronic pancreatitis (CP), its contribution to the etiology and development of pancreatitis is still shrouded in mystery in many respects [ 1 , 2 , 3 , 4 ]. Since the discovery of the first CP-causing variant, namely c.365G>A (p.Arg122His) in the PRSS1 gene (MIM# 276000; encoding cationic trypsinogen) [ 5 ], one new puzzle has emerged pertaining to whether or how a particular genetic risk factor interacts with alcohol consumption to cause CP.…”
Section: Introductionmentioning
confidence: 99%
“…PERT use increased to 55.7% in this subgroup of 9,541 although adequate dosing remained low at 36.9%. Second, although the prevalence of alcohol use in CP cohorts is 44%‐68%, 10 the authors reported alcoholism in just 20%. This could reflect under‐reporting of alcohol consumption, but also implies over‐estimation of CP diagnosis thereby offsetting the PERT requirement.…”
Section: Chronic Pancreatitis (N = 37 061) Pancreatic Cancer (N mentioning
confidence: 94%